Synthesis and Antiinflammatory Activity of Some New Benzoxazole Derivatives - Waghulde, Sandeep; Patil, V.R.; Chaudhari, R.Y.; Fegade, J.D.; Bhole, R.P. (Asian Journal of Chemistry, 2010)
A series of some new 5-substituted benzoxazoles were synthesized and were characterized by elemental analysis, IR, 1H NMR and mass spectra. These compounds were also screened for its antiinflammatory activity.